Belis Ivory in the Lamaholot Tradition - Kristoforus Laga Kleden,; Tomy Michael,; Melania Ajeng Surya Putri,; Angelina Bernadina L Keban,; Sinta Andhani Pou,; Ester Johana Elisabeth, (Technium Social Sciences Journal, 2021)
This research method uses normative and empirical. At the normative level, namely using the existing literature and at the empirical level with data directly from the interviewees, including the webinar that was held on November 7, 2020. Belis is a very important element in the marriage customs of the people in NTT, especially in Lamaholot. The giving of belis by the prospective groom to the prospective bride isn’t only for proposing but also a symbol of the unification of the family of the prospective groom and also the family of the prospective woman. Belis ivory elephant is belis that has the most important meaning. However, in giving the elephant ivory belis, social status greatly affects this. The higher the social status of women, the more elephant ivory belis given.